2023
DOI: 10.1021/acsbiomaterials.3c00014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Supramolecular Interactions between the Extracellular-Matrix-Derived Minimalist Bioactive Peptide and Nanofibrillar Cellulose for the Development of an Advanced Biomolecular Scaffold

Abstract: It has been increasingly evident over the last few years that bioactive peptide hydrogels in conjugation with polymer hydrogels are emerging as a new class of supramolecular materials suitable for various biomedical applications owing to their specificity, tunability, and nontoxicity toward the biological system. Despite their unique biocompatible features, both polymer- and peptide-based scaffolds suffer from certain limitations, which restrict their use toward developing efficient matrices for controlling ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
(228 reference statements)
0
7
0
Order By: Relevance
“…Alamar Blue, a specific fluorescence indicating dye, is used to assess cellular proliferation on the composite hydrogel in different time periods. , The detail study is reported in our earlier literatures. ,, Cellular proliferation was carried out at different intervals of 48, 72, and 120 h. In particular, triplicate studies of this experiment were done to get the averaged data which can be represented as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alamar Blue, a specific fluorescence indicating dye, is used to assess cellular proliferation on the composite hydrogel in different time periods. , The detail study is reported in our earlier literatures. ,, Cellular proliferation was carried out at different intervals of 48, 72, and 120 h. In particular, triplicate studies of this experiment were done to get the averaged data which can be represented as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…47,48 The detail study is reported in our earlier literatures. 11,21,48 Cellular proliferation was carried out at different intervals of 48, 72, and 120 h. In particular, triplicate studies of this experiment were done to get the averaged data which can be represented as mean ± SD.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogelators comprising peptides constitute a key element in the central dogma of global health care avenues. The impressive amalgamation of properties such as biodegradability, biocompatibility, low cytotoxicity, and ability to mimic natural proteins makes them remarkable candidates for the design of advanced synthons with diversified applicabilities like drug delivery, tissue engineering, effluent management, antimicrobial, wound dressing, and many more. …”
Section: Introductionmentioning
confidence: 99%